Weisheng-tang protects against ischemic brain injury by modulating microglia activation through the P2Y12 receptor - Kim, Min Jae; Lee, Dohee; Ryu, Ji Hye; Lee, Seo-Yeon; Choi, Byung Tae; Yun, Young Ju; Shin, Hwa Kyoung (Frontiers in Pharmacology, 2024)
Stroke, a leading cause of death and disability, lacks effective treatments. Post-stroke secondary damage worsens the brain microenvironment, further exacerbating brain injury. Microglia's role in responding to stroke-induced damage in peri-infarct regions is crucial. In this study, we explored Weisheng-tang's potential to enhance ischemic outcomes by targeting microglia. We induced middle cerebral artery occlusion and reperfusion in mice, followed by behavioral assessments and infarct volume analyses after 48 h, and examined the changes in microglial morphology through skeleton analysis. Weisheng-tang (300 mg/kg) significantly reduced infarction volume and alleviated neurological and motor deficits. The number of activated microglia was markedly increased within the peri-infarct territory, which was significantly reversed by Weisheng-tang. Microglial morphology analysis revealed that microglial processes were retracted owing to ischemic damage but were restored in Weisheng-tang-treated mice. This restoration was accompanied by the expression of the purinergic P2Y12 receptor (P2Y12R), a key regulator of microglial process extension. Weisheng-tang increased neuronal Kv2.1 clusters while suppressing juxtaneuronal microglial activation. The P2Y12R inhibitor-ticagrelor-eliminated the tissue and functional recovery that had been observed with Weisheng-tang after ischemic damage. Altogether, Weisheng-tang improved experimental stroke outcomes by modulating microglial morphology through P2Y12R, shedding light on its neuroprotective potential in ischemic stroke.